Enhanced photocatalytic hydrogen production under visible light over a material based on magnesium ferrite derived from layered double hydroxides (LDHs). (26th May 2014) - Zazoua, H.; Boudjemaa, A.; Chebout, R.; Bachari, K.
SUMMARY The magnesium ferrite derived from layered double hydroxides (molar ratio Mg/Fe = 2), synthesized by coprecipitation method is found to be an active photocatalyst for hydrogen production from water under visible light. The structural, morphological, and optical properties of the material are characterized by powder X‐ray diffraction, scanning electron microscopy, and Fourier transform infrared and UV‐Vis diffuse reflectance spectroscopy. The results indicated that the material has small particles with a diameter of ~1.8 nm and a specific surface area above 60 m2 g−1. The optical properties revealed semiconducting properties with band gap energy of 1.74 eV, showing an efficient visible light absorption. The cyclic voltammetry indicated that the photoelectrochemical response of the material is characterized by type p conductivity. Furthermore, the solid exhibited a high photoactivity toward the reduction of water, which is attributed to the efficient separation and transportation of the photogenerated charge carriers. Under visible light, the best performance is achieved at pH 10 with a hydrogen liberation amount and quantum efficiency of 223 mol and 0.5%, respectively, after 1 h of irradiation. Copyright © 2014 John Wiley & Sons, Ltd.